2015
DOI: 10.1007/s00109-015-1313-z
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin attenuates liver fibrosis by inducing nitric oxide production of hepatic stellate cells

Abstract: • Adiponectin activates HSC iNOS/NO and SEC eNOS/NO systems. • Adiponectin inhibits HSC proliferation and migration but promotes its apoptosis. • Adiponectin inhibits CCL4-induced liver fibrosis by modulation of liver iNOS/NO. • Adiponectin stimulates HSC iNOS/NO via adipoR2-AMPK-JNK/ErK1/2-NF-κB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…However, a potential metabolic role of aquaporins in HSCs beyond the water transport has not been investigated. As previously reported in different models, we could show here that adiponectin downregulates several genes involved in liver fibrosis and HSCs activation such as TGFB1, COL1A1, and FN1. However, in accordance to upregulation of the glycerol transporter AQP3, we found upregulation of genes involved in lipogenesis (PPARG and DGAT1) together with increased HSC lipid content.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, a potential metabolic role of aquaporins in HSCs beyond the water transport has not been investigated. As previously reported in different models, we could show here that adiponectin downregulates several genes involved in liver fibrosis and HSCs activation such as TGFB1, COL1A1, and FN1. However, in accordance to upregulation of the glycerol transporter AQP3, we found upregulation of genes involved in lipogenesis (PPARG and DGAT1) together with increased HSC lipid content.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, we further analyzed the action of adiponectin on HSCs in two directions: first with respect to lipid metabolism that is related to glycerol shuttling, second, HSC activation, emphasizing how its action would turn HSCs into quiescent cells preserving and protecting from liver diseases. We and others have shown that adiponectin action could partially reverse HSCs activation. In addition, we show here a dramatic increase in glycerol uptake and lipid content by adiponectin stimulated HSC, indicating a metabolic impact of AQP3 upregulation.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, endothelial dysfunction and reduced NO production have been found to precede inflammation and fibrosis in a NAFLD rat model [13]. In contrast, activation of eNOS as well as increased NO production ameliorates the progression of NASH-related hepatic fibrosis [36, 37]. We previously demonstrated the amplifying effects of the Met-Leu combination on AMPK signaling and reduction of hepatic steatosis in DIO-mice [12].…”
Section: Discussionmentioning
confidence: 99%
“…And the elevated serum adiponectin levels might be related to inflammatory status in the pathogenesis of RA [31]. In addition to the role of adiponectin in inflammation, there is increasing evidences which indicate that adiponectin is also an important regulator in tissue remodeling and fibrosis, and adiponectin seems to be antifibrogenic in tissue fibrosis [33][34][35]. In fibrosis of SSc, myofibroblasts activation and collagen production are the most [36].…”
Section: Discussionmentioning
confidence: 99%